2022
DOI: 10.1111/1755-0998.13668
|View full text |Cite
|
Sign up to set email alerts
|

The complete and closed genome of the facultative generalist Candidatus Endoriftia persephone from deep‐sea hydrothermal vents

Abstract: The mutualistic interactions between Riftia pachyptila and its endosymbiont Candidatus Endoriftia persephone (short Endoriftia) have been extensively researched. However, the closed Endoriftia genome is still lacking. Here, by employing single‐molecule real‐time sequencing we present the closed chromosomal sequence of Endoriftia. In contrast to theoretical predictions of enlarged and mobile genetic element‐rich genomes related to facultative endosymbionts, the closed Endoriftia genome is streamlined with fewer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 174 publications
0
16
0
Order By: Relevance
“…Prior measurements which we compare our data against ( Figure 1 , Table S2 ) are bacterial (Form II, Form I’) or Cyanobacterial (Form I) rubisco measurements, where a pure enzyme, substrate-depletion assay such as ours was performed on well-characterized strains where rubisco was obtained through expression and subsequent purification from E. coli . We also included one Form II measurement from a Riftia pachyptila symbiont, Candidatus Endoriftia Persephone [ 44 ], where rubisco was purified from the host trophosome because at the time of the measurement the symbiont could not be cultured separately from the host, though a complete genome has recently been published [ 45 ]. Therefore, we did not include measurements where a non-native bacterial rubisco was expressed by another organism in vivo and KIE calculated by extrapolating ratios of intracellular to extracellular CO 2 [ 46 ], nor measurements from plants or the Solemya velum symbiont because it is not a member of the Cyanobacteria [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior measurements which we compare our data against ( Figure 1 , Table S2 ) are bacterial (Form II, Form I’) or Cyanobacterial (Form I) rubisco measurements, where a pure enzyme, substrate-depletion assay such as ours was performed on well-characterized strains where rubisco was obtained through expression and subsequent purification from E. coli . We also included one Form II measurement from a Riftia pachyptila symbiont, Candidatus Endoriftia Persephone [ 44 ], where rubisco was purified from the host trophosome because at the time of the measurement the symbiont could not be cultured separately from the host, though a complete genome has recently been published [ 45 ]. Therefore, we did not include measurements where a non-native bacterial rubisco was expressed by another organism in vivo and KIE calculated by extrapolating ratios of intracellular to extracellular CO 2 [ 46 ], nor measurements from plants or the Solemya velum symbiont because it is not a member of the Cyanobacteria [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…fitAB , higAB , vapBC , algRZ ) as well as outer membrane porins ( ompA-F ; Supplementary Table 3 ). The discovery of flagella genes in the A. adamantis symbiont genome is surprising as these genes are typically abundant in campylobacterial, but not gammaproteobacterial Alviniconcha symbiont genomes ( Beinart et al 2019 ), though are observed in some other symbiotic Gammaproteobacteria, including those of tubeworms and mussels ( Robidart et al 2008 ; Egas et al 2012 ; Gardebrecht et al 2012 ; De Oliveira et al 2022 ). The presence of flagella-encoding loci could suggest that the biology of the A. adamantis symbiosis is markedly different from other gammaproteobacterial associations in Alviniconcha and has closer resemblance to Campylobacteria-dominated systems, where flagella have been implicated in host specificity, nutrient transfer and/or continuous symbiont transmission ( Sanders et al 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of DNA methylation together with genes required for methylation were found in EPR9N genome but this epigenetic system do not appear to be ubiquitous amongst deep-sea chemosynthetic symbionts. Indeed, the genome of the tubeworm symbiont Candidatus Endorifita persephone, which like the B. thermophilus symbiont has high host-specificity, does not seem to be methylated and the methyltansferase genes it encodes appear to be inactivated by mobile elements 91 . This raises questions about the role of epigenetics in host-associated and free-living contexts, and about the evolutive consequences of transitioning towards stricter host-specificity on the symbiont ecology.…”
Section: Discussionmentioning
confidence: 99%